STUDI PENGGUNAAN GESCHOOL DALAM PEMBELAJARAN SENI BUDAYA MATERI SENI RUPA KELAS VIII SMP NEGERI 11 PADANG - Lindri Inggriani; Yahya Yahya (Serupa The Journal of Art Education, 2021)
This study aims to 1) Knowing the learning process through the application of Geschool in the subjects of fine arts material art class VIII SMP Negeri 11 Padang, 2) Knowing the benefits on the subjects of art and culture fine arts material grade VIII SMP Negeri 11 Padang. This type of research is descriptive qualitative. Data types use primary and secondary data. Data collection techniques in this research are observation, interview and documentation. The steps to analyze data are data collection, data reduction, data presentation and inference. Based on the results of the research, it was concluded that the learning process through geschool application in art and culture subjects of fine arts material grade VIII SMP Negeri 11 Padang went well and was very helped, which from the geschool has helped add new menus in the application. Geschool helps teachers evaluate students about the material being studied. In the assignment, teachers have also been greatly helped by the existence of learning materials provided by MGMP in accordance with KI KD. The benefit of implementing Geschool in art and culture subjects of fine arts material grade VIII SMP Negeri 11 Padang is that teachers can directly share student material easily without taking a long time and geschool application also facilitates the tryout assessment process, teachers no longer need to check the learning results manually and made it easier to assign assignments to students. Students are disciplined in using time because the application is arranged according to the hours of the lesson, students and parents can also know directly the results of the learning and the teacher no longer checks the absence manually anymore because in the geschool application will be seen students who are following the learning and the teacher only monitors the students online.Keywords: use, geschool, cultural arts fine arts material